Six Sigma-Mumbai Dabbawalas’ Story Redefines Theory - Gupta, Atul (Indian Journal of Marketing, 2007)
’Dissatisfy your customers’-All world class companies are trying to dissatisfy current expectations of their existing customers through continuously improving their value creation and delivery processes, not only satisfying them through quality products and services only but trying to maintain quality long term relationships through perfection in every thing they do to be world class. It is better to eliminate defects in your products and service delivery’s quality rather than trying to minimize final defective outputs. Although through better inspection and quality control mechanisms, you can satisfy your end users by simply delivering only non defective products but what about cost, time and precious human power wasted in making defective products? Yes, this is going to affect your bottom line. Today in the era of cut throat competition, you need not to only satisfy your external customers but all stakeholders e.g. Employees, shareholders, govt., suppliers and value network partner’s etc. For that you need to have quality products and services at lowest possible cost, saving interest of all stakeholders and that is possible only through organization wide changes in way of doing all business activities and processes tuned to perfection in terms of outcome with zero defects to satisfy customers needs profitably. Therefore, Top management is redefining processes through using quantifiable and statistically measurable goals of each and every process keeping customer’s satisfaction in mind and trying to minimize duplication of human efforts and eliminating defective processes to reach a pre-determined benchmark level of quality that can be measured, evaluated and controlled. One of successfully deployed element of Total Quality Management (TQM) initiatives is Six sigma.